Distribution, abundance, and conservation of Vinaceous Amazons (Amazona vinacea) in Argentina and Paraguay - Cockle, Kristina Louise (2007)
Vinaceous Amazons (Amazona vinacea) are endemic to the Atlantic forest of southeastern Brazil, eastern Paraguay, and the province of Misiones in Argentina. We searched for Vinaceous Amazons throughout the western part of its range in Argentina and Paraguay during 1639 days of fieldwork from 1997 to 2006. These parrots have disappeared from most areas where they were historically recorded in these countries, and are now limited to a few sites in northeastern Paraguay and central Misiones (Argentina). We estimate the minimum remaining populations at 220 individuals in Paraguay and 203 individuals in Argentina. Important sites for the species are (1) the farming area from San Pedro to Tobuna (Misiones, Argentina) and (2) the Itaipú reserves complex and Reserva Natural Privada Itabó (Paraguay). In our surveys, Vinaceous Amazons were absent from the largest tracts of forest in Misiones, and were most often observed feeding, roosting, and nesting in small forest remnants and in agricultural areas that included forest fragments and isolated trees. Threats to amazons in these areas include nest poaching, forest clearing, and being shot as a crop pest. We confirmed 40 Vinaceous Amazons kept as pets in 35 homes between San Pedro and Tobuna. Environmental education and law enforcement are urgently needed to reduce threats in populated areas, and subsistence farmers need technical and logistical support to slow or stop the conversion of forest into cropland. Finally, additional study is needed to determine this amazon's habitat preferences, nest site requirements, and demography in different habitats.